2021
DOI: 10.1037/apl0000813
|View full text |Cite
|
Sign up to set email alerts
|

To thine own (empowered) self be true: Aligning social hierarchy motivation and leader behavior.

Abstract: Research to date has advanced opposing viewpoints on whether leaders who are psychologically empowered support the autonomy of their subordinates or engage in controlling leader behaviors. Our integration of research on empowerment and social hierarchy suggests that leaders’ feelings of empowerment can promote autonomy-supporting and/or controlling leader behaviors, contingent on the leaders’ prestige and dominance motivations, respectively. Our findings demonstrate that, among leaders high (vs. low) in presti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 96 publications
0
30
0
Order By: Relevance
“…From early work on the subject, such as French and Raven's five bases of power (French & Raven, 1959), to Kipnis et al's eight-factor influence tactics model (1980) and Fiedler's contingency model (Fiedler, 1978), all have proposed an array of behavioral responses that managers adopt to influence others. We extend this work by incorporating an evolutionary grounded dual rank framework of achieving social rank or influence in a group that classifies leader influence along two different hierarchical orientations-dominance and prestige-each associated with its own set of cognitions, motivations, and influence strategies (Cheng et al, 2013;Henrich & Gil-White, 2001;Lee et al, 2020). Dominance-based behavioral patterns entail being assertive, decisive, confident, and sometimes forceful when interacting with others (Maner & Case, 2016).…”
Section: Theory Two Alternative Ways To Influencementioning
confidence: 99%
See 1 more Smart Citation
“…From early work on the subject, such as French and Raven's five bases of power (French & Raven, 1959), to Kipnis et al's eight-factor influence tactics model (1980) and Fiedler's contingency model (Fiedler, 1978), all have proposed an array of behavioral responses that managers adopt to influence others. We extend this work by incorporating an evolutionary grounded dual rank framework of achieving social rank or influence in a group that classifies leader influence along two different hierarchical orientations-dominance and prestige-each associated with its own set of cognitions, motivations, and influence strategies (Cheng et al, 2013;Henrich & Gil-White, 2001;Lee et al, 2020). Dominance-based behavioral patterns entail being assertive, decisive, confident, and sometimes forceful when interacting with others (Maner & Case, 2016).…”
Section: Theory Two Alternative Ways To Influencementioning
confidence: 99%
“…However, having a formal leadership role or authority position emboldens such individuals to enact these tendencies further, given the discretion afforded by their formal position. For instance, in an organizational context, leaders who feel psychologically empowered and are high (vs. low) on dominance engage in more controlling behavior toward their subordinates by ensuring that they obey their instructions, berating them if they fail to accomplish their tasks, and preventing them from having the final say in meetings or decisions (Lee et al, 2020). Hence, dominance may encapsulate multiple styles of leadership driven by an underlying drive to control others 1 .…”
Section: Theorymentioning
confidence: 99%
“…Motivation activities in empowering women are very important in providing entrepreneurial provisions in the target group. Lee et al (2020) showed that empowerment efforts in the social hierarchy then show the role of a leader. Providing motivation is one of the keys to a leader who plays a close role in empowerment efforts to continue to be able to improve and develop the capabilities of the community group he is leading.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, in the context of lower TIRQ, these individuals can experience higher image risk than they do under conditions of higher TIRQ. When higher-status individuals feel a heightened sense of image risk, this psychological burden can lead them to utilize a variety of impression management tactics that they would not otherwise engage in to maintain a desirable image and avoid a loss in status (Lee et al, 2020; Pettit et al, 2010, 2016). Further supporting this effect, under unstable or otherwise threatening conditions, higher-status group members tend to experience greater status maintenance concerns (Marr & Thau, 2014; Raz et al, 2020) and become more cautious in their behaviors toward others (Doyle et al, 2016; Hays & Blader, 2017; Kim et al, 2019).…”
Section: Theory and Hypothesesmentioning
confidence: 99%